2020
DOI: 10.1109/access.2020.2988122
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Forest Changes in Korean Peninsula Using Landsat Images During 1990–2015: A Comparative Study of Two Neighboring Countries

Abstract: Forest change in the Korean Peninsula related to different socioeconomic developments in North and South Korea and impacted on the regional environment. However, there was a lack of consistent information about forest changes, especially comparative knowledge of North and South Korea that support management and policymaking. We used the change object update method to generate the first object-based 30m land cover set for the peninsula and analyzed new observations of forest changes in North and South Korea fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Our previous work accumulated 311 unchanged samples that could be used to assess the accuracy [16,17]. In addition, through stratified sampling, we supplemented 677 samples by inspecting Google Earth images with very-high-resolution [24,37]. The accuracy of maps for 2004,2006,2009,2011,2012,2013,2014,2016,2017,2018, and 2019 was assessed because of an insufficient amount of very-high-resolution images.…”
Section: Data and Methods For Accuracy Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work accumulated 311 unchanged samples that could be used to assess the accuracy [16,17]. In addition, through stratified sampling, we supplemented 677 samples by inspecting Google Earth images with very-high-resolution [24,37]. The accuracy of maps for 2004,2006,2009,2011,2012,2013,2014,2016,2017,2018, and 2019 was assessed because of an insufficient amount of very-high-resolution images.…”
Section: Data and Methods For Accuracy Assessmentmentioning
confidence: 99%
“…Previous studies indicated the effectiveness of decision rules, such as in mapping paddy rice and urban settlement [24,36]. Nonetheless, the multiple rules integration, namely MDR that orderly extracts LCLU [37,38], has not been effectively applied in GEE. This study applied and packaged MDR as an effective classifier in GEE to observe land dynamics, namely annual LCLUC [14].…”
Section: Integration Of Automatic Thresholding and Multilevel Decision Rule Processmentioning
confidence: 99%
See 3 more Smart Citations